Chloroplast‐targeted bacterial RecA proteins confer tolerance to chloroplast DNA damage by methyl viologen or UV‐C radiation in tobacco (Nicotiana tabacum) plants. Issue 2 (9th July 2012) - Jeon, Hyesung; Jin, Yong‐Mei; Choi, Mi Hwa; Lee, Hyeyun; Kim, Minkyun
<x xml:space="preserve">Abstract</x> The nature and importance of the DNA repair system in the chloroplasts of higher plants under oxidative stress or UV radiation‐induced genotoxicity was investigated via gain‐of‐functional approaches exploiting bacterial RecAs. For this purpose, transgenic tobacco (Nicotiana tabacum) plants and cell suspensions overexpressing Escherichia coli or Pseudomonas aeruginosa RecA fused to a chloroplast‐targeting transit peptide were first produced. The transgenic tobacco plants maintained higher amounts of chloroplast DNA compared with wild‐type (WT) upon treatments with methyl viologen (MV), a herbicide that generates reactive oxygen species (ROS) in chloroplasts. Consistent with these results, the transgenic tobacco leaves showed less bleaching than WT following MV exposure. Similarly, the MV‐treated transgenic Arabidopsis plants overexpressing the chloroplast RecA homologue RECA1 showed weak bleaching, while the recA1 mutant showed opposite results upon MV treatment. In addition, when exposed to UV‐C radiation, the dark‐grown E. coli RecA‐overexpressing transgenic tobacco cell suspensions, but not their WT counterparts, resumed growth and greening after the recovery period under light conditions. Measurements of UV radiation‐induced chloroplast DNA damage using DraI assays (Harlow et al. 1994) with the chloroplast rbcL DNA probe and quantitative PCR analyses showed that the transgenic cell suspensions better repaired their UV‐C radiation‐induced chloroplast DNA lesions compared with WT. Taken all together, it was concluded that RecA‐overexpressing transgenic plants are endowed with an increased chloroplast DNA maintenance capacity and enhanced repair activities, and consequently have a higher survival tolerance to genotoxic stresses. These observations are made possible by the functional compatibility of the bacterial RecAs in chloroplasts.